2010
DOI: 10.1097/qai.0b013e3181caebaa
|View full text |Cite
|
Sign up to set email alerts
|

Tenofovir-Linked Hyperparathyroidism Is Independently Associated With the Presence of Vitamin D Deficiency

Abstract: 25(OH) VDD is associated with tenofovir-linked hyperparathyroidism and also with higher eGFR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
58
3
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 8 publications
11
58
3
3
Order By: Relevance
“…63 Moreover, nonnucleoside reverse transcriptase inhibitor and protease inhibitor treatment puts patients at risk of elevated parathyroid hormone levels, 63 as shown with tenofovirlinked hyperparathyroidism, which is closely linked to vitamin D deficiency. 69 However, vitamin D status did not affect CD4 cell recovery after initiation of highly active antiretroviral therapy. 63 Host defense against human T-lymphotropic virus type 1 (HTLV-1) hinges on an effective Th1 response.…”
Section: Antimicrobial Efficacy Against Different Infective Agentsmentioning
confidence: 99%
“…63 Moreover, nonnucleoside reverse transcriptase inhibitor and protease inhibitor treatment puts patients at risk of elevated parathyroid hormone levels, 63 as shown with tenofovirlinked hyperparathyroidism, which is closely linked to vitamin D deficiency. 69 However, vitamin D status did not affect CD4 cell recovery after initiation of highly active antiretroviral therapy. 63 Host defense against human T-lymphotropic virus type 1 (HTLV-1) hinges on an effective Th1 response.…”
Section: Antimicrobial Efficacy Against Different Infective Agentsmentioning
confidence: 99%
“…The phosphaturic hormone fibroblast growth factor 23 (FGF23) is not altered by TDF use (18,19). TDFassociated bone changes may occur through a TDF effect on parathyroid hormone (16,20), as parathyroid hormone secretion increases soon after initiating TDF (21). Vitamin D deficiency (22) may exacerbate this increase in parathyroid hormone (20,23), but TDF-associated increased parathyroid hormone is found even in persons with sufficient vitamin D (24).…”
mentioning
confidence: 99%
“…42,60 In some studies designed for the purpose, PTH concentration or prevalence of sHPTH was found to be consistently associated with 25OHD level and/or ART therapy (PIs and NNRTIs). 7,34,36,[39][40][41][42]45,51 Three articles, in particular, found a correlation between tenofovir use and higher parathyroid hormone concentrations. 7,36,39 In addition, Masia et al evaluated changes in PTH after the initiation of two different ART regimens.…”
Section: Secondary Hyperparathyroidism and Parathyroid Hormone Statusmentioning
confidence: 99%
“…7,34,36,[39][40][41][42]45,51 Three articles, in particular, found a correlation between tenofovir use and higher parathyroid hormone concentrations. 7,36,39 In addition, Masia et al evaluated changes in PTH after the initiation of two different ART regimens. 7 Both regimens produced significant increases in PTH concentration, and in the proportion of patients presenting with sHPTH during the follow-up period.…”
Section: Secondary Hyperparathyroidism and Parathyroid Hormone Statusmentioning
confidence: 99%
See 1 more Smart Citation